Twin to twin transfusion syndrome - Bhatt, R (Kathmandu University Medical Journal, 2010)
Twin to twin transfusion syndrome (TTTS) is a specific condition complicating 10-15% of monochorionic multiple pregnancy. Intertwin vascular anastomoses and transfusion is a normal event. Syndrome develops when blood flow is unbalanced. Recent studies suggest a paucity of bi-directional superficial anastomoses failing to compensate for hemodynamic imbalance resulting from unidirectional transfusion along deeper arterio-venous anastomoses. TTTS is associated with high rates of perinatal mortality. Acute and chronic forms exist and severity varies. The donor twin is often smaller, hypovolemic, anemic and develops congestive heart failure. The recipient is usually heavier and polycythemic. Antenatally, second trimester ultrasound usually detects the condition. Serial amnioreduction is the recommended therapy. Postnatally, intertwin haemoglobin and birth weight differences along with pallor in one twin and plethora in the other are helpful in making a diagnosis. Medical care of twins after birth is directed towards problem related to anemia, polycythemia and hydrops. Review of the syndrome is presented with an illustrative case. Key words: Twin to twin transfusion syndrome; Neonatal diagnosis; Symptomatic polycythemia; Partial exchange transfusion DOI: 10.3126/kumj.v8i1.3228 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 87-90